2019
DOI: 10.1101/837294
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

B Cell Receptor-Responsive miR-141 and viral miR-BART9 promote Epstein-Barr Virus Reactivation Through FOXO3 Inhibition

Abstract: 6Antigen recognition by the B cell receptor (BCR) is a physiological trigger for reactivation of Epstein-Barr virus 7(EBV) and can be recapitulated in vitro by cross-linking of surface immunoglobulins. Previously, we identified a 8 subset of EBV microRNAs (miRNAs) that attenuate BCR signal transduction and subsequently, dampen lytic 9replication in B cells. The roles of host miRNAs in virus reactivation are not completely understood. To 10 investigate this process, we profiled the small RNAs in latently infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 78 publications
(101 reference statements)
1
0
0
Order By: Relevance
“…In addition, we also found that both BART7 and BART9 mutants display an increased expression of the viral genes encoding the lytic proteins ZTA and gp350 (BLZF1 and BLLF1, respectively). EBV BART9 was reported to attenuate and regulate the EBV lytic cycle via transcriptional inhibition of several components of the BCR and FOXO3 signaling pathway, showing striking sequence homology to the human miRNA miR-141 (hsa-miR-141) [27,28]. Our results support the hypothesis that the expression of BART7 and BART9 are associated with regulating cell proliferation, apoptosis and maintaining the viral latency in B-cells.…”
Section: Discussionsupporting
confidence: 83%
“…In addition, we also found that both BART7 and BART9 mutants display an increased expression of the viral genes encoding the lytic proteins ZTA and gp350 (BLZF1 and BLLF1, respectively). EBV BART9 was reported to attenuate and regulate the EBV lytic cycle via transcriptional inhibition of several components of the BCR and FOXO3 signaling pathway, showing striking sequence homology to the human miRNA miR-141 (hsa-miR-141) [27,28]. Our results support the hypothesis that the expression of BART7 and BART9 are associated with regulating cell proliferation, apoptosis and maintaining the viral latency in B-cells.…”
Section: Discussionsupporting
confidence: 83%